Successful Subungual Glomus Tumur Removal: A Case Report and Future Guidance on Diagnosis and Treatment - Made Bramantya Karna; Richard Christian Suteja (University Library System, University of Pittsburgh, 2024)
Background: Glomus tumors are rare benign hamartomas of the glomus body that occur mostly - though not limited to - the distal phalanxes of the digits. This article provides a real-life example of successful rare disease identification and treatment. It also provides a guideline that may help serve as future guidance on diagnosis and treatment. Case: A 41-year-old male came into our hospital presenting a chief complaint pain of episodes of throbbing pain, which has occurred spontaneously on the left thumb for the past two years. The pain was said to worsen in the past two weeks. The patient was positive for Hildreth's, Love's pin, and cold sensitivity tests. The previous x-ray showed no abnormalities in the left thumb. MRI found a hyperdense subungual lesion in the dorsal interphalangeal joint of the left thumb. We then performed an excision using the transungual approach. Histopathological findings found a relatively well-circumscribed lesion of the glomus apparatus absent of abnormal mitosis and necrosis. Two months after the excision, the patient reported no symptoms of recurrency, nail deformity, or other adverse outcomes. Conclusion: Patients typically present a chief complaint of chronic paroxysmal throbbing nail pain that persists for years, increases following exposure to cold environments, and is disproportionately exacerbated due to the slightest touch. Hildreth's, Love's Pin, and cold sensitivity Test were special examinations that elicit or suppress pain. As with most benign tumors, complete excision usually yields good results. Adequate knowledge about diagnostic methods will help patients achieve early intervention and resolvent.